Anthropometric protocols for the construction of new international fetal and newborn growth standards: the INTERGROWTH‐21st Project. (11th July 2013) - Cheikh Ismail, L; Knight, HE; Bhutta, Z; Chumlea, WC
Abstract : The primary aim of the INTERGROWTH‐21 st Project is to construct new, prescriptive standards describing optimal fetal and preterm postnatal growth. The anthropometric measurements include the head circumference, recumbent length and weight of the infants, and the stature and weight of the parents. In such a large, international, multicentre project, it is critical that all study sites follow standardised protocols to ensure maximal validity of the growth and nutrition indicators used. This paper describes, in detail, the selection of anthropometric personnel, equipment, and measurement and calibration protocols used to construct the new standards. Implementing these protocols at each study site ensures that the anthropometric data are of the highest quality to construct the international standards.